Das Vorgebirge: Entwicklung und Struktur einer Gartenbaulandschaft am Rande des Verdichtungsraumes Rhein-Ruhr - Böhm, Hans (ERDKUNDE, 1981)
On the south-western edge of the Rhine-Ruhr agglomeration there is a landscape zone in which the cultivation of specialized crops is of outstanding significance. The locational development of this area is traced from its utilization in the first half of the19th century to the present times. At the same time v. Thunen’s partial location factor model is examined in respect of its suitability for the explanation of agrarian spatial ordering. This is possible for the period 1820-1900. in the 20th century, however, the conditions of production and market outlets changed as a result of competition from peripheral locations. The number of competing locations increases together with the advanced development of cooling techniques and the integration of European agricultural markets. In the inner German market traditional market gardens experience strong competition from large and medium-sized farms, which have introduced large-scale mechanized vegetable production. These changes have the effect of making individual firms opt for increasingly horizontal specialization in different branches of horticulture. Those who are orientated towards services and ultimate consumers prefer locations in the vicinity of a local retail market. The remaining firms no longer produce for a market area in the classical sense, but for a distribution organisation which has to take into account the demands of the intermediate trade for the greatest possible diversification and a quantitatively constant supply.